The Blind Ophthalmologist: A Theological Study of Revelation 3:14-22 - Korsah, Effah Kwaku; Boaheng, Isaac (Universitas PGRI Madiun, 2023)
The only church Jesus does not commend among the seven churches of Asia is the Church of Laodicea. This is as strange as it calls for a critical look at the problem of the church. As an expansion of the existing studies on the text to Laodicea, this theological study investigates the content of the letter to the church of Laodicea in Revelation 3:14-22 to identify the church’s core problem and the central message it carries. The study examines the theological understanding of the key imagery Jesus employs to describe Laodicea’s church. The main argument is that the major problem of the church is the lack of perception, and the focus of the message lies in the caution that being spiritually indifferent is perilous, but even worse is the peril that lies in being oblivious to one's spiritual state due to a shift of focus from Jesus.